Conjugated Polyelectrolyte/Graphene Hetero‐Bilayer Nanocomposites Exhibit Temperature Switchable Type of Conductivity. (3rd January 2017) - Brus, Viktor V.; Gluba, Marc A.; Mai, Cheng‐Kang; Fronk, Stephanie L.; Rappich, Jörg; Nickel, Norbert H.; Bazan, Guillermo C.
Abstract : The majority of charge carriers in conjugated polyelectrolyte (CPE)‐PyrBIm4 /graphene hetero‐bilayers can be dynamically changed from electrons to holes, and vice versa, within a temperature range of 60 °C. Doping mechanisms under consideration include charge transfer from structural units in the CPE‐PyrBIm4 backbone and/or field‐effect doping from adjacent ionic functionalities. A new concept of the graphene/CPE/Au thermobarristor is proposed and practically realized.